Middle Permian ostracods (Crustacea) from the Guadalupe Mountains, West Texas, USA - Tarnac, Anaëlle; Forel, Marie-Béatrice; Nestell, Galina; Nestell, Merlynd; Crasquin, Sylvie (European Journal of Taxonomy, 2021)
Middle Permian (Guadalupian) ostracods are described from the Williams Ranch Member of the Cutoff Formation (Roadian) and the McKittrick Canyon Member of the Bell Canyon Formation (Capitanian) from two sections exposed in Culberson County, Guadalupe Mountains, West Texas. Their taxonomy is discussed and adds to the scientific understanding of marine ostracod biodiversity and palaeobiogeography during the Middle Permian. Ostracod assemblages are represented by 51 species of 26 genera and 15 families. Eleven species are newly described: Healdia mckittrickensis Crasquin sp. nov., Healdia cutoffella Crasquin sp. nov., Aurikirkbya guadalupensis Crasquin sp. nov., Hollinella (Hollinella) williamsranchensis Crasquin sp. nov., Geisina culbersonensis Crasquin sp. nov., Paraparchites pecosensis Crasquin sp. nov., Bairdia elcapitanensis Forel sp. nov., Ceratobairdia mescaleroella Forel sp. nov., Ceratobairdia sexagintaduella Forel sp. nov., Ceratobairdia pratti Forel sp. nov., and Denticupachydomella bellcanyonensis Forel sp. nov. The diagnosis of the genus Denticupachydomella is emended. The palaeobiogeographic distribution of the species is analyzed and exemplifies the taxon exchanges between Tethyan and Panthalassic localities in the Permian. The eastern margin of the Palaeo-Tethyan realm is shown to have played a major role in radiation of taxa in the Permian.